Searching for anomalous top quark interactions with proton tagging and timing detectors at the LHC - Baldenegro, Cristian; Bellora, Andrea; Fichet, Sylvain [UNESP]; von Gersdorff, Gero; Pitt, Michael; Royon, Christophe (Springer Nature, 2022)
We study the LHC sensitivity to new broad neutral resonances produced in two-photon fusion and decaying to a top quark pair, γγ → tt¯. This is probed in central exclusive tt¯ production in proton-proton collisions, pp → ptt¯ p. We use the tagging of the intact protons by PPS (CMS) and AFP (ATLAS) and consider the semi-leptonic tt¯ channel. The sensitivity is also mapped onto a set of dimension-8 γγtt¯ operators in the large mass limit. Using the kinematical correlations between the intact protons and the reconstructed tt¯ system, we obtain a sensitivity to the couplings of the dimension-8 operators of 1.4 10−11 GeV−4 at 95% CL. The sensitivity to the anomalous couplings is significantly improved down to about 7 10−12 GeV−4 if the proton time-of-flight is known with a precision of 20 ps in future measurements. The 95% CL sensitivity to broad neutral resonances reaches masses of order 1500 GeV when using timing information.
Keywords: Axions and ALPs; Other Weak Scale BSM Models; Specific BSM Phenomenol- ogy; Top Quark